Color Guard Body Exercise Form for Dancers' Body Endurance - Wahyuning Tiyas (Journal of Dance and Dance Education Studies, 2023)
Physical exercise for a dancer is a form of basic training activity that is carried out regularly and sequentially, covering the muscles, joints and all parts of the body. The function of physical exercise is to prepare a body that is not yet ready to be ready for dance activities. The aim of this research is to explain the color guard form of exercise and its relevance to dancers' endurance. The research method used is a qualitative descriptive-analytical method with data sources through observation, interviews,and documentation studies. Color Guard is a division in a marching band that specializes in displaying visual beauty. Based on research results, Color Gu ard is based on physical exercise to train flexibility and endurance. The color guard form of exercise can be applied to dancers, especially for flexibility and endurance training. Body movements include: 1) Position, 2)Saute, 3)Plie, 4) GroundPlie,5)Rond De Jambe, 6)Pase, 7)Pirouttes, 8)Turning, 9)Jazz run, 10)Grand Jette, 11)Plank, 12)Split. Exercise color guard Used to strengthen leg muscles and train flexibility. For dancers, having strong legs is the key to being able to dance both traditional and contemporary modern. Exercise color guard relevant for training the endurance and flexibility of the dancer's body in line with the increasing endurance of the dancer's body marked by increasing training intensity from time to time.